1974
DOI: 10.1079/bjn19740055
|View full text |Cite
|
Sign up to set email alerts
|

Protein quality of some unusual protein foodstuffs. Studies on the African locust-bean seed (Parkia filicoidea Welw.)

Abstract: I. The proximate composition, amino acid composition and the quality of the protein of the African locust-bean (Purkiu jilicoideu Welw.) seed, seed with pulp, and various processed forms, with or without amino acid supplementation, were assessed.2. The crude protein content of the locust-bean seed was 303 g/kg and the crude fibre content was IZI g/kg.3. The seeds contained (mg/g protein): 67 lysine, 6.1 methionine and 8.9 tryptophan. 4. Diets containing IOO g protein/kg supplied by the seed did not support gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
1

Year Published

1977
1977
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 5 publications
3
25
1
Order By: Relevance
“…This is much higher than the seeds (49.49%) as reported by Fetuga et al (1974); and is in agreement with the findings of Uwaegbute (1996) t hat t he fruit pulp contains more carbohydrates than the seeds. It is also higher than most legume seeds with only lentils and bambara groundnuts coming close with a value of 65.0% (Muller, 1988).…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…This is much higher than the seeds (49.49%) as reported by Fetuga et al (1974); and is in agreement with the findings of Uwaegbute (1996) t hat t he fruit pulp contains more carbohydrates than the seeds. It is also higher than most legume seeds with only lentils and bambara groundnuts coming close with a value of 65.0% (Muller, 1988).…”
Section: Introductionsupporting
confidence: 81%
“…In the search for plant protein and vitamin substitutes, the African locust bean (Parkia biglobosa) has found very popular use especially in the fermented 'dawadawa' form, which is a product of the seeds However, the yellow dry powdery fruit pulp called 'Dorowa' in Hausa has not attracted much attention. Many workers (Fetuga et al 1974;CampbellPlatt,1980;Eka, 1980;Odunfa,1986;Oke and Umoh, 1987) have reported the nutritional adequacy of the African locust bean seeds with a proximate composition of 30.00% protein, 15.00% fat, 4.00% crude fiber, 2.00% ash and 49.00% carbohydrate. According to Uwaegbute (1996) the powdery fruit pulp contains more carbohydrate than the seeds, the carbohydrates being primarily reducing sugars (19.00%), nonreducing sugars (9.00%) and other complex carbohydrates (36.00%).…”
Section: Introductionmentioning
confidence: 99%
“…The husks and pods are good feed for livestock (Obizoba, 1998). Fetuga et al (1974) reported the plant to be a good source of tannins, saponins, gums, fuel and wood. The seeds of various species of the genus Parkia have been investigated for their protein and amino acid contents.…”
Section: Introductionmentioning
confidence: 99%
“…The pods are flat, large, irregular clusters from which the locust bean seeds are obtained (Omafuvbe et al, 2004). It contains about 40.4% protein, 31.5% fat, 3.1% fibre and 15% carbohydrate (Fetuga et al, 1974). The African locust bean is consumed mainly because of the flavouring attributes.…”
Section: Introductionmentioning
confidence: 99%